The Directional Thermal Diffusivity of Rattans of Benin, Ghana and Nigeria by The Regular Regime Method - SIMENOU, Dagbégnon; AWANTO, CHRISTOPHE; VODOUNNOU, Edmond; VIANOU, COKOU ANTOINE (My University, 2018)
The use of wood products as furniture for the manufacture becomes more and more important over the years. At the same time, the vegetation cover of the sub region is undergoing a severe degradation which seriously compromises the environment. The use of non-timber forest products such as bamboo and rattan in furnishings and even reinforcement in civil engineering of the physical characterization of rattans from Ghana, Nigeria imported to Benin and Benin, we have emphasized the directional thermal diffusivity of rattans in Benin, Ghana and Nigeria by the regular regime method. We’ve obtained respective for axial and radial diffusivity the following results in case of: Benin rattan: 0.033192 and 0.653326 m2s-110-6; Nigerian rattan: 0.032164 and 0.641273 m2s-110-6 ; Ghana rattan: 0.316815 and 0.616851 m2s-110-6. Those results obtained were compared with those already existing for some woody species. They confirmed not only the validity of our experimental system but also the relevance of the regular regime for the measurement of diffusivity. So, the rattan has a lower radial and respective axial diffusivity than teak (0.242 and 0.143) m2s- 110-6, ebony (0.228 and 0.176) m2s-110-6, and the copolymer (0.354 and 0.133) m2s-110-6 Rattan has a lower radial and respective axial diffusivity than teak (0.242 and 0.143) m2s-110-6, ebony (0.228 and 0.176) m2s- 110-6, and the copolymer (0.354 and 0.133) m2s-110-6.
Keywords: Rattan; Regime Method; Thermal Diffusivity